Swallowing, communication and quality of life outcomes in case of hemi-glossectomy: a case study - Gaikwad, Bhumi A.; Mohite, Jyoti S.; Thakar, Mitali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
The current article discusses about the assessment and detailed traditional therapeutic management in case of hemi-glossectomy patient. It also highlights how the glossectomy changes have an impact on the person’s psychological status; it is also an important aspect to be worked upon in therapy. With various traditional swallowing techniques along with postural and consistencies alterations helped patient to consume from thin liquids to soft solids oral feeds. The present article also talks about improvement in the speech intelligibility that was affected as a consequence of hemi-glossectomy.